The Potential of Marine Ecotourism in Pandan Beach, Districts Central Tapanuli, Province of North Sumatera - Nabila, Amelia; Nasution, Syafruddin; Siregar, Yusni Ikhwan (Journal of Coastal and Ocean Sciences, 2021)
Marine ecotourism is a type of special interest tourism that has marine-related activities, both under the sea and above sea level. Marine ecotourism can be one of the key factors in supporting the protection of cultural values that live in society, sustainability, and the quality of the environment. In tourism development, there are two approaches, namely mass tourism development and sustainable tourism. The study was conducted in February - April 2021 on the Pandan Beach of Central Tapanuli Regency, the Province of North Sumatera. The aims of the study were to determine the marine ecotourism potential and to know the perception of stakeholders. The method used in this study is a survey method, with respondents comprising of local people, tourists, business tourism, and policymakers. Water measuring observed includes water brightness, temperature, salinity, acidity (pH), and the flow velocity carried. The results showed that the tourist attraction at Pandan Beach includes enjoying the panorama, sunset, traditional culinary, sports activity, mangrove and the ecologically at Pandan Beach is white sand with clear waters and have beautiful panorama with lush pine tree vegetation, as well as activities that can be done such as fishing, swimming, boating, and walking around the beach. Tourism Suitability Index values at stations I, II, and III were 96%, 95%, and 71%, respectively. Pandan Beach has the potential as a marine ecotourism area such as natural beauty that is pristine, natural and so exotic.